Nitrogen fertilizer equivalencies of organics of differing quality and optimum combination with organic nitrogen source in Central Kenya - Kimetu, J.M.; Mugendi, DN; Palm, Cheryl A.; Mutuo, PK; Gachengo, CN; Bationo, B. André (Springer, 2004)
Decline in crop yields is a major problem facing smallholder farmers in Kenya and the entire Sub-Saharan region. This is attributed mainly to the mining of major nutrients due to continuous cropping without addition of adequate external nutrients. In most cases inorganic fertilizers are expensive, hence unaffordable to most smallholder farmers. Although organic nutrient sources are available, information about their potential use is scanty. A field experiment was set up in the sub-humid highlands of Kenya to establish the chemical fertilizer equivalency values of different organic materials based on their quality. The experiment consisted of maize plots to which freshly collected leaves of Tithonia diversifolia (tithonia), Senna spectabilis (senna) and Calliandra calothyrsus (calliandra) (all with %N>3) obtained from hedgerows grown ex situ (biomass transfer) and urea (inorganic nitrogen source) were applied. Results obtained for the cumulative above ground biomass yield for three seasons indicated that a combination of both organic and inorganic nutrient source gave higher maize biomass yield than when each was applied separately. Above ground biomass yield production in maize (t ha?1) from organic and inorganic fertilization was in the order of senna+urea (31.2), tithonia+urea (29.4), calliandra+urea (29.3), tithonia (28.6), senna (27.9), urea (27.4), calliandra (25.9), and control (22.5) for three cumulative seasons. On average, the three organic materials (calliandra, senna and tithonia) gave fertilizer equivalency values for the nitrogen contained in them of 50, 87 and 118%, respectively. It is therefore recommended that tithonia biomass be used in place of mineral fertilizer as a source of nitrogen. The high equivalency values can be attributed to the synergetic effects of nutrient supply, and improved moisture and soil physical conditions of the mulch. However, for sustainable agricultural production, combination with mineral fertilizer would be the best option.